Improving mental healthcare access and experience for people from minority ethnic groups: an England-wide multisite experience-based codesign (EBCD) study - Winsper, C; Bhattacharya, R; Bhui, K (BMJ Publishing Group, 2023)
Background Long-standing ethnic inequalities in access and mental healthcare were worsened by the COVID-19 pandemic.